Log-Based Code Maniac E-Learning Web Development Model Utilizing Adaptive Web Development Techniques - Reko Syarif Hidayatullah (International Journal Software Engineering and Computer Science (IJSECS), 2025)
Education is a fundamental requirement for human civilization, particularly for children and adolescents. The recent pandemic has compelled the education sector to adopt online learning alternatives. Codemaniac is an e-learning tool developed with gamification techniques to enhance student motivation. However, Codemaniac still lacks adaptive features that optimize user engagement based on individual behaviors. To address this limitation, further development will incorporate adaptive features by utilizing recorded user behavior from log files. This behavioral data will be clustered using the fuzzy c-means algorithm, resulting in three distinct user groups, each receiving a tailored user interface. The system is developed following the SDLC waterfall model, with Python used for clustering implementation. The development process involves three user roles, five additional functional requirements, and one non-functional requirement. System testing employs white-box methods for unit testing and black-box methods for validation.